Comparative study to evaluate the efficacy and safety of oral Mifepristone versus intracervical Dinoprostone gel for induction of labour and their effects on fetomaternal outcome - Pathak, Anu; Singh, Saroj; Singh, Shikha; Kumar, Rajesh; Tyagi, Arpita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Mifepristone and Dinoprostone are used in inducing labour in pregnancy by acting as cervical ripening drugs. A randomized case control study to evaluate the efficacy, safety and fetomaternal outcome of induction of labour with oral Mifepristone and intracervical Dinoprostone gel was done. Methods: About 300 patients were included after taking informed consent. 150 patients were placed in each group A and B. In group A patients received 200 mg oral Mifepristone tablet and in group B 0.5 mg Dinoprostone gel was given intracervically and 2nd dose was repeated after 6 hours later if adequate uterine contractions were not achieved. A detailed analysis was carried out in both groups regarding efficacy and safety of drugs in terms of necessity of augmentation of labour with oxytocin, induction to delivery interval, fetal outcome in terms of NICU admission. Results: 59.33% cases in Mifepristone group and 72% case in Dinoprostone group required augmentation with oxytocin. Mean induction delivery interval in Mifepristone group in primigravida was 17.998±1.128 hrs and mean induction delievery interval in multigravida was 11.648±1.112 hours. 88% cases in mifipristone group and 80% cases in Dinoprostone group delivered vaginally. NICU admission was 1.33% in Mifepristone group and 2.66% in PGE2 gel group. Conclusions: Mifepristone when compared with intracervical Dinoprostone gel, acts as a better cervical ripening agent and requires lesser need for Oxytocin augmentation. Though, mean induction delivery interval was more with Mifepistone, the incidence of successful vaginal delivery was higher as compared to Dinoprostone.